ANATOMY AND CONFLICT RESOLUTION APPROACH TO SOCIOLOGY: THE STUDY OF THE RELIGIOUS CONFLICTS OF THE AHMADIYYA CONGREGATION IN SUKABUMI DISTRICT - Yusuf, Yusuf (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
This study was conducted to analyze the anatomy of a religious conflict in particular related to the conflict of the Ahmadiyya in Sukabumi and religious conflict resolution particularly in Sukabumi Ahmadiyya with sociological approaches as a means of mediation. The election is carried as a sociological approach to settling the conflicts which are selected based on a variety of considerations that the approach that has been done by the parties to put forward more mediator the legal aspects, the results are less effective. Legal approaches in religious conflicts in Sukabumi constellations into two mutually contradictory sides between the religious law is seen as the absolute power of God by positive law which was seen as the result of human which sometimes in disregard of religious fanaticism by. This study uses a qualitative method and a case study approach based on Cresswell's theory. The results showed that 1) the anatomy of the Ahmadiyya religious Congregations conflict happening in the Sukabumi can be seen from the cause of the onset of the conflict, the parties in conflict, the onset of the conflict, and the impact of the onset of the conflict. Impacts of the onset of the conflict, namely suspicion between the more powerful group, the two groups feel aggrieved at each other, the loss of religious tolerance and community, the destruction of the unity and the unity of the community, regional development is hampered. (2) religious conflict Mediation between Ahmadiyya Congregation with Non-Ahmadiyya in Sukabumi carried through; The formation of Team Handlers JAI by MUI, the Attorney, TNI, POLRI, Kodim Sukabumi, Socializing schools of true religion by MUI, Socialization harmony and unity of the nation by TNI AD, hospitality to the parties by Babinsa, Babinsa as mediators, conducting joint activities, the addition of the local Koramil post.